The sleep-first effect of perampanel in children with self-limited epilepsy with centrotemporal spikes: A temporal efficacy analysis in the context of complex polytherapy - Biao Jiang; Ninger Zhang; Xiaoli Shao (PLoS ONE, 2026)
This single-center, retrospective observational study aimed to investigate the temporal sequence of the effects of Perampanel (PER) on seizure control, sleep architecture, and sleep quality in children with Self-Limited Epilepsy with Centrotemporal Spikes (SeLECTS). Thirty-one children (mean age 6.8 ± 2.45 years) with a monthly seizure frequency of ≥1 and significant sleep disturbances (Children’s Sleep Habits Questionnaire [CSHQ] score >41) were enrolled. Assessments of sleep architecture (via 24-hour ambulatory EEG), subjective sleep quality (CSHQ), and seizure frequency were conducted at baseline, 1 month, and 2 months after PER initiation. The results revealed that PER treatment led to significant improvements in sleep architecture and subjective sleep quality as early as 1 month, characterized by a decrease in N1 stage duration and increases in N3 and REM stage durations (all P < 0.01). In contrast, significant reductions in both monthly seizure frequency and the Spike-Wave Index (SWI) were predominantly observed at the 2-month mark, with 93.5% of children achieving a ≥50% reduction in seizure frequency. PER was well-tolerated, and no serious adverse events were reported during the study period. This pattern where sleep benefits manifested early and stabilized, while seizure control demonstrated a more protracted improvement suggests a potential temporal dissociation in the therapeutic effects of PER. In conclusion, PER is effective and well-tolerated in improving sleep and reducing seizures in children with SeLECTS. The modulation of sleep structure may be an important early mechanism associated with its therapeutic effects, with sleep quality serving as a potential early predictor of treatment response.